DENSE: DiElectric Novel Soil Evaluation System to Electrochemically Profile Soil Matrices. Issue 6 (1st June 2022) - Dhamu, Vikram Narayanan; Paul, Anirban; Muthukumar, Sriram; Prasad, Shalini
Abstract : Soil health and quality monitoring in the near past has been highly qualitative and speculative with more recent advancements still trying to fill the void of a holistic soil profile. In this work, an electrochemical approach has been proposed to build a unique quantitative model—"DENSE" that probes the soil diffuse double layer (DDL) dielectric to evaluate a thorough interfacial profile of the soil matrix. Room Temperature Ionic Liquid (RTIL) thin film was employed to modify the electrode probe to leverage as an effective transducer for a system driven by electrostatic interactions and charged diffusive behavior. The soil is surveyed based on fundamental understandings of electrochemistry and thereby obtaining equivalent metrics using chronoamperometry, electrochemical impedance spectroscopy and chronocoulometry modalities to determine interfacial characteristics at the soil-water double layer. Capacitive dominant nature is exhibited in more coarse-drier soils similar to a case of non-faradaic electrochemical characteristics while the presence of water in the composite system seems to induce a slightly more charge transfer behavior indicative of mobile electrochemically active species. This gives a fundamental discernibility between the soil physico-chemical state corresponding to the output that is modelled using an impedemetric circuit fit and serves as a soil dielectric probing mechanism.